Improving non-technical skills (teamwork) in post-partum haemorrhage: A grouped randomised trial. (October 2017) - Letchworth, Pippa M.; Duffy, Shane P.; Phillips, Dan
Abstract: Objective: To determine the effect of a decision support technology on teamwork and associated non-technical (NTS) and technical skills when teams manage post-partum haemorrhage (PPH) in the simulated environment. Methods: Multidisciplinary (MDT) maternity teams were taught how to manage post partum haemorrhage. They were randomised to the intervention: using a decision support mobile digital platform or a control group. Each team managed a post-partum simulation, which was recorded and reviewed by assessors. Primary outcome measures to assess teams NTS were the validated Global Assessment of Obstetric Team Performance (GAOTP) and Clinical Teamwork Scale (CTS). Secondary outcome measures were the 'friends and family test', technical skills, and the System Usability Scale (SUS). Sample size estimation was calculated by using 80% power 5% significance two tailed test (p1 = 85% p2 = 40%) n = 34. Results: 38 teams from August 2014–February 2016, were recruited, technical issues with failure of recording equipment meant 4 teams were excluded from teamwork analysis (1 intervention 3 control). Teamwork improved across all domains with the intervention (using a decision support mobile digital platform) p < 0.01. CTS improved between 6.7–16.8% (average 14.2%) and GAOTP between 8.6–17.1% (average 13.5%) for all domains. Using the control group as baseline, the intervention improved teamwork by 25% using CTS and 22% using GAOTP. Fewer technical skills were missed with the intervention (p < 0.01). There was no statistical difference in the time technical skills were achieved. Assessors were more likely to recommend intervention teams 87.5% (77/88) than control teams 63.6% (56/88) p < 0.01 to their friends or family. The SUS was 'Good' (69) becoming excellently 'Usable' (81.6) over the study period. Conclusion: We report a decision support system, which improved NTS when managing PPH. Lack of teamwork is often cited as the cause of failures in care and we report a usable technology that assists with and improves teamwork during an emergency.